ANALISIS PERBANDINGAN BIAYA OPERASIONAL KENDARAAN (BOK) JALAN LINGKAR AMBARAWA DAN JALAN EKSISTING - Subandriyo, Eko; Marpaung, Ridho Roni; Ismiyati, Ismiyati; Kushardjoko, Wahyudi (Jurnal Karya Teknik Sipil, 2014)
Developments in the area Ambarawa showed increased very rapidly, as shown by the many activities of the trip reset - shuttle from Semarang - Yogyakarta, passing Ambarawa. Barriers of time and is very important to know because it is the minimum travel time for a vehicle to the place of destination. As we know often times it happens that so long queue of vehicles caused by several factors during the journey, such as the existence of market centers along the road, not signalized intersections and also the driver's lack of discipline have contributed to the low road. Barriers of this trip will be a negative impact, such as in the form of lost time due to the long trip and the increase in vehicle operating costs (VOC) to the existing road. The purpose of this evaluation is to analyze the velocity space (space mean speed) and the Vehicle Operating Cost comparison Ambarawa ring road and the existing road. The calculation of Vehicle Operating Costs (VOC) using the formula for the ring road Pacific Consultant International (PCI) and using the formula in the existing road curve Vehicle Speed. This is because the ring road are relatively few barriers while relatively many barriers existing road. So using a different method for determining vehicle operating costs. From the analysis of the average velocity (space mean speed) it can be seen that the travel time through the streets ring with a distance of 7.3 miles faster than the road with a distance of 6.5 km eksisiting this can be seen from the average velocity (space mean speed) vehicles both cars (58.52 km / h), buses (52.36 km / h) and a truck (47.67 km / h) faster past the ring road ring road vehicles as cars, buses and trucks are not a lot of experience travel barriers. The results of the comparison vehicle operating cost (VOC), obtained past the ring road Ambarawa cost more frugal when dibandingankan the existing road. Where the economic value of automobiles Rp 415.11 (3.09%); truck Rp 2321.46 (4.01%), and buses Rp 3383.27 (8.49%). This is because as the value of travel time on the ring road is more economical than the existing road, so it is recommended the diversion of heavy vehicles (class IIA and IIB) have to go through the roundabout Ambarawa so will reduce the volume of vehicles passing through the existing road also to be more economical in spending operational and can reduce travel time for goods brought more quickly to the destination.